Hubungan Kemitraan Antara Sekolah Menengah Kejuruan dengan Industri - Anjani Alicia Azcha; Rina Febriana; Cucu Cahyana; Constantinus Rudy Prihantoro; Muhammad Nurtanto (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Vocational High Schools (SMK) and the industrial world have a close symbiotic relationship in producing competent graduates for the workforce needed by industrial factories as a qualified resource. However, the main challenge still faced is the gap (mismatch) between graduate competencies and the expectations of the World of Work and the World of Industry (DUDI). The purpose of this study is to describe the strategic role and pattern of partnership relationships between vocational schools and industrial partners. This research method is a literature study using data collected over the past five years as study material in the research. The results show that the involvement of industrial partners through curriculum synchronization, industrial class programs, teaching factories, and Industrial Work Practices (Prakerin) as a means of preparing students for the transition from the world of education to the world of industry. The success of this continuity is also built on a foundation of trust and communication between schools and industrial managers. The impact of a strong partnership will significantly improve students' hard skills and soft skills. This study emphasizes the importance of the role of industry as an external validator to ensure graduates have relevant competitiveness and adaptability to technological changes to ensure continuity between schools and the industrial world.